Unraveling the impact of upfront chemotherapy and proton beam therapy on treatment outcome and follow-up in central nervous system germ cell tumors: a single center experience - Del Baldo, Giada; Vennarini, Sabina; Toniutti, Maristella; Abbas, Rachid; Lorentini, Stefano; Piccirilli, Eleonora; Cacchione, Antonella; Megaro, Giacomina; Di Ruscio, Valentina; De Ioris, Maria Antonietta; De Salvo, Andrea; Albino, Giulia; et al. (Frontiers in Oncology, 2023)
Background: Germ cell tumors (GCT) account for a minority of central nervous system (CNS) malignancies, highly prevalent in adolescents and young adults. Despite their aggressive biological behavior, prognosis is excellent in most cases with risk stratified treatment, consisting in a combination of chemotherapy and radiotherapy. Whole ventricular irradiation (WVI) and craniospinal irradiation, the treatment of choice for localized and metastatic disease, pose significant risk of collateral effects, therefore proton beam radiation (PBT) has been recently proposed for its steep dose fallout. Materials and methods: We report our experience in a consecutive series of 17 patients treated for CNS GCT at our Institution from 2015 to 2021. Results: Most frequent lesion location were sellar/suprasellar (35%) and bifocal germinoma (35%), followed by pineal (18%) and thalamic (12%). Two patients (12%), had evidence of disseminated disease at the time of diagnosis. At the latest follow-up all but one patient showed complete response to treatment. The only relapse was successfully rescued by additional chemotherapy and PBT. PBT was well tolerated in all cases. No visual, neurological or endocrinological worsening was documented during and after treatment. Neuropsychological evaluation demonstrated preservation of cognitive performance after PBT treatment. Conclusions: Our data, albeit preliminary, strongly support the favourable therapeutic profile of PBT for the treatment of CNS germ cell tumors.